EKSPLORASI DEDAK PADI SEBAGAI PAKAN LOKAL: EVALUASI KUALITAS FISIK DAN ORGANOLEPTIK DEDAK PADI DI KABUPATEN TANAH LAUT, KALIMANTAN SELATAN: EXPLORATION OF RICE BRAN AS LOCAL FEED: EVALUATION OF PHYSICAL AND ORGANOLEPTIC ATTRIBUTES IN TANAH LAUT, SOUTH KALIMANTAN - Rifqi Hidayatulloh; Muhammad Irvan Ali; Baluh Medyabrata Atmaja; Amelia Lulu Rosalin Hutabarat; Wenni Meika Lestari; Abdul Muta Ali; Akmad Rio Padilah; Alief Rahmania Safitri (Universitas Boyolali, 2026)
Rice bran, an important byproduct of the milling process, has enormous potential as a source of local feed ingredients. This research aims to evaluate the physical quality and organoleptic parameters of rice bran to ensure the availability of quality local feed. The research method used is the survey method with a purposive sampling technique, and the data obtained were analyzed descriptively. The findings of this study are expected to provide insights into the optimal use of rice bran in animal feed formulations. By assessing its nutritional value and overall quality, this research could contribute to more sustainable feeding practices in the local agriculture sector. The results show that the best physical quality of rice bran is found in the sub-districts of Panyipatan, Bajuin, and Batu Ampar, which meet the ideal specific gravity and bulk density ranges for use as feed ingredients. In contrast, Tambang Ulang and Kurau have relatively lower values for some parameters, requiring further processing before optimal application. Rice bran from most sub-districts in Tanah Laut Regency is considered suitable for use as feed raw material.